Personalized learning system for visualizing knowledge structures and recommending study materials links. (January 2019) - Nitchot, Athitaya; Wettayaprasit, Wiphada; Gilbert, Lester
The aim of this research is to introduce a method of constructing knowledge structures which represent the relationships among the knowledge items in a pedagogically useful way. A prototype, "MyTeLeMap, " was implemented to support both learners and instructors. Learners could visualize the knowledge structures of different knowledge domains and obtain links to corresponding study materials. The system also offered learning paths and recommendations, for example, to related structures. Instructors could create and share their knowledge structures. An experiment compared the learning outcomes of learners using MyTeLeMap and those using a free-browsing mode. The results showed that MyTeLeMap helped learners more than free browsing. Future work includes the incorporation of a search application for learners and of management features for instructors to upload and share learning materials linked to specific knowledge domains.